MEDIA PEMBELAJARAN KOMPOSISI FOTO DIGITAL PADA SISWA KELAS XI PROGRAM KEAHLIAN MULTIMEDIA SMK MUHAMMADIYAH 1 LAMONGAN - Kurnia Yahya (Joutica, 2017)
Digital Photo Composition is one of the competencies that must be mastered by students in completing learning in Multimedia Vocational High School. Digital Photo Composition is a very important part in the world of graphic design. To master this competence requires a deep understanding. In the delivery of the material either theoretically or practicum of a teacher should really be able to attract students sympathy that students finally feel comfortable and motivated in learning. Interactive Media Learning DIGITAL PHOTOGRAPHY used to take Competency Standard Composition Digital Photos, In this learning media, learners will learn from knowing the parts of the camera to the process of photo editing. It consists of interactive content and includes animations, videos, text, photos and simulations. There is also a random evaluation for the answer as well as the scoring system at the end of the evaluation. This media is expected to be a learning material for the students mengasikkan mengasikkan and ultimately students can understand and able even without any learning in the classroom